Membrane Lipid Requirements of the Lysine Transporter Lyp1 from Saccharomyces cerevisiae. Issue 14 (26th June 2020) - van 't Klooster, Joury S.; Cheng, Tan-Yun; Sikkema, Hendrik R.; Jeucken, Aike; Moody, D. Branch; Poolman, Bert
Abstract: Membrane lipids act as solvents and functional cofactors for integral membrane proteins. The yeast plasma membrane is unusual in that it may have a high lipid order, which coincides with low passive permeability for small molecules and a slow lateral diffusion of proteins. Yet, membrane proteins whose functions require altered conformation must have flexibility within membranes. We have determined the molecular composition of yeast plasma membrane lipids located within a defined diameter of model proteins, including the APC-superfamily lysine transporter Lyp1. We now use the composition of lipids that naturally surround Lyp1 to guide testing of lipids that support the normal functioning of the transporter, when reconstituted in vesicles of defined lipid composition. We find that phosphatidylserine and ergosterol are essential for Lyp1 function, and the transport activity displays a sigmoidal relationship with the concentration of these lipids. Non-bilayer lipids stimulate transport activity, but different types are interchangeable. Remarkably, Lyp1 requires a relatively high fraction of lipids with one or more unsaturated acyl chains. The transport data and predictions of the periprotein lipidome of Lyp1 support a new model in which a narrow band of lipids immediately surrounding the transmembrane stalk of a model protein allows conformational changes in the protein. Graphical Abstract: Unlabelled Image Highlights: Membrane reconstitution of an amino acid transporter from the yeast plasma membrane Lipid dependence of the lysine transporter Lyp1, a member of the APC superfamily The lysine transporter requires phosphatidylserine and ergosterol for activity. Lipids with one or more unsaturated acyl chains are required for transport. Non-bilayer lipids stimulate transport, but phosphatidylethanolamine is not essential.